2013
DOI: 10.1371/journal.pone.0054132
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Reference Genes for Quantitative RT-PCR in Ascending Aortic Aneurysms

Abstract: Hypertension and congenital aortic valve malformations are frequent causes of ascending aortic aneurysms. The molecular mechanisms of aneurysm formation under these circumstances are not well understood. Reference genes for gene activity studies in aortic tissue that are not influenced by aortic valve morphology and its hemodynamic consequences, aortic dilatation, hypertension, or antihypertensive medication are not available so far. This study determines genes in ascending aortic tissue that are independent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 21 publications
(22 reference statements)
2
16
3
Order By: Relevance
“…PCR conditions and primer sequences used were previously described [11]. Following recent guidelines PPIA [12], beta-actin, and GADPH were used as candidate reference genes.…”
Section: Rt-pcr Validationmentioning
confidence: 99%
“…PCR conditions and primer sequences used were previously described [11]. Following recent guidelines PPIA [12], beta-actin, and GADPH were used as candidate reference genes.…”
Section: Rt-pcr Validationmentioning
confidence: 99%
“…Quantification of gene expression was performed in duplicate by quantitative real-time PCR using Taqman probes (See online supplementary material table S3). Gene expression was normalised against EIF2β1, a gene highly suitable for TAA materials,20 and relative gene expression calculated using the 2 -ΔΔCt -method.…”
Section: Methodsmentioning
confidence: 99%
“…β-Actin , G3pdh , β2m ) are commonly used with this purpose. However, numerous studies have reported that the expression levels of classical reference genes are not stable in many tissues under certain physiological conditions, making them inadequate for gene expression normalization [ 19 , 22 25 ]. Accordingly, it is recognized that, in order to obtain reliable data using RT-qPCR analyses, the stability of the housekeeping gene chosen for the experimental setup must be previously demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…A key aspect of the method is the normalization of mRNA concentrations with housekeeping or reference genes [ 18 , 19 ], the stability of which must be confirmed in the tissue employed in order to obtain accurate data [ 18 , 20 , 21 ]. However, several common reference genes are frequently used in RT-qPCR assays without further validation, even though they have been found unstable in different tissues and physiological conditions [ 19 , 22 24 ], including the dilated ascending aorta [ 25 ].…”
Section: Introductionmentioning
confidence: 99%